UMAR BAKRI” DALAM KARYA SENI LUKIS REALIS KONTEMPORER - PRADANA HIDAYAT, Drs. Idran Wakidi, M.Pd., Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2018)
This final work aims to visualize “Umar Bakri” in the works of contemporary realist painting. Master is an unsung hero, her position in respectable in society, and many of the challenges and obstacles that a teacher must confront. The method of creation of this final paper uses five stages: preparation stage, elaboration stage, synthesis stage, and concept realization phase begins sketching, sketching move, tool and material preparation, process of work and finishing. The final stage is the completion to the exhibition.Keywords: “Umar Bakri”, Art, Contemporary Realist.